Proyecto de factibilidad para la implementación de una microempresa productora y comercializadora de lámparas a base de coco en el cantón Zapotillo provincia de Loja - Godos Vélez, Digna Isabel (2017)
This study entitled "Project of feasibility for the implementation of a microenterprise producer and marketer of lamps based COCO in the CANTON ZAPOTILLO province of LOJA" has as its main objective implement a company in the canton for a sustainable development in this corner of the country. The methodology used for this thesis project was: The analytical method, descriptive, inductive, deductive and statistical and the techniques used were the survey and interview. In relation to the market study, a sample of 357 families of Zapotillo was applied, establishing a potential demand of 3,340 families, real demand of 2,984 families and an effective demand of 2,517 families, which determined, a demand an effective demand of 4,406 Lamps and an offer of 60 lamps per year, applied 2 offer, which has determined an unsatisfied demand of 4,346 lamps. The technical study has determined the size of the plant capacity installed of 4320 and used 3036 annual lamps, located in the canton Zapotillo. In the study organizational it company is established legally as DISAGO Cia. Ltda. relying on charts, both the structural, positional and functional and the respective functions manual. The financial aspect, requires an investment of $10.219,52, which is funded by the 51,07% with own capital and 48,93% with a credit granted by BanEcuador, with a rate of interest of 10% and 5-year. The financial evaluation States that the project is feasible, with the following results: the VAN is $. 29188,63; 96,13% IRR; B/c ratio is 1.25 dollars; a sensitivity in the increase in the costs of the 16,65% and a decrease in the income of the 13,37%, the PRC is it will make in 2 years 1 months and 17 days. And as a final part of this work arises conclusions and recommendations. Keywords: crafts, lighting, entrepreneurship, feasibility.